Natural Dam Lake Cuejdel in the Stânişoarei Mountains, Eastern Carpathians A Limnogeographical Study - Mihu-Pintilie, Alin (Springer International Publishing, 2018)
This book presents an interdisciplinary study of Lake Cuejdel, one of the youngest natural dam lakes in Romania. Even though the overall study has a strong geographical approach, it also includes limnological and hydrological studies. The lake was formed in two phases: Initially a small lake appeared in 1978, and then in 1991 a major landslide occurred that blocked the Cuejdel brook and a larger lake was formed. The book covers various topics, including the lacustrine basin, the geological setting, analyses of the physical-chemical parameters, water dynamics, flora and fauna and lake management. This book is of interest for those working in freshwater science and ecology, physical geography, hydrology and limnology.